Next-generation panel sequencing identifies NF1 germline mutations in three patients with pheochromocytoma but no clinical diagnosis of neurofibromatosis type 1. Issue 2 (February 2018) - Gieldon, Laura; Masjkur, Jimmy Rusdian; Richter, Susan; Därr, Roland; Lahera, Marcos; Aust, Daniela; Zeugner, Silke; Rump, Andreas; Hackmann, Karl; Tzschach, Andreas; Januszewicz, Andrzej; Prejbisz, Aleksander; et al.
Abstract : Objective: Our objective was to improve molecular diagnostics in patients with hereditary pheochromocytoma and paraganglioma (PPGL) by using next-generation sequencing (NGS) multi-gene panel analysis. Derived from this study, we here present three cases that were diagnosed with NF1 germline mutations but did not have a prior clinical diagnosis of neurofibromatosis type 1 (NF1). Design: We performed genetic analysis of known tumor predisposition genes, including NF1, using a multi-gene NGS enrichment-based panel applied to a total of 1029 PPGL patients. We did not exclude genes known to cause clinically defined syndromes such as NF1 based on missing phenotypic expression as is commonly practiced. Methods: Genetic analysis was performed using NGS (TruSight Cancer Panel/customized panel by Illumina) for analyzing patients' blood and tumor samples. Validation was carried out by Sanger sequencing. Results: Within our cohort, three patients, who were identified to carry pathogenic NF1 germline mutations, attracted attention, since none of the patients had a clinical suspicion of NF1 and one of them was initially suspected to have MEN2A syndrome due to co-occurrence of a medullary thyroid carcinoma. In these cases, one splice site, one stop and one frameshift mutation in NF1 were identified. Conclusions: Since phenotypical presentation of NF1 is highly variable, we suggest analysis of the NF1 gene also in PPGL patients who do not meet diagnostic NF1 criteria. Co-occurrence of medullary thyroid carcinoma and PPGL was found to be a clinical decoy in NF1 diagnostics. These observations underline the value of multi-gene panel NGS for PPGL patients.